Spectrophotometric Assay of Salbutamol Sulphate in Pharmaceutical Preparations by Coupling with Diazotized ρ-bromoaniline - Tamathir et al. (مجلة بغداد للعلوم, 2019)
In this research, salbutamol sulphate (SAS) has been determined by a simple, rapid and sensitive spectrophotometric method. Salbutamol sulphate in this method is based on the coupling of SAS with diazotized ρ- bromoaniline reagent in alkaline medium of Triton X-100 (Tx) to form an orange azo dye which is stable and water-soluble. The azo dye is exhibiting maximum absorption at 441 nm. A 10 - 800 µg of SAS is obeyed of Beer's law in a final volume of 20 ml, i.e., 0.5- 40 ppm with ε, the molar absorptivity of 48558 L.mol-1.cm-1 and Sandell's sensitivity index of 0.01188 µg.cm-2. This new method does not need solvent extraction or temperature control which is well applied to determine SAS in different types of pharmaceutical preparations.